Image-Based Genome-Wide siRNA Screen Identifies Selective Autophagy Factors - Orvedahl, Anthony (2011)
Selective autophagy involves the recognition and targeting of specific cargo, such as damaged organelles, misfolded proteins, or invading pathogens for lysosomal destruction(1–4). Yeast genetic screens have identified proteins required for different forms of selective autophagy, including cytoplasm-to-vacuole targeting, pexophagy, and mitophagy, and mammalian genetic screens have identified proteins required for autophagy regulation(5). However, there have been no systematic approaches to identify molecular determinants of selective autophagy in mammalian cells. To identify mammalian genes required for selective autophagy, we performed a high-content, image-based, genome-wide siRNA screen to detect genes required for the colocalization of Sindbis virus capsid protein with autophagolysosomes. We identified 141 candidate genes required for viral autophagy, which were enriched for cellular pathways related to mRNA processing, interferon signaling, vesicle trafficking, cytoskeletal motor function, and metabolism. Ninety-six of these genes were also required for Parkin-mediated mitophagy, indicating that common molecular determinants may be involved in autophagic targeting of viral nucleocapsids and autophagic targeting of damaged mitochondria. Murine embryonic fibroblasts lacking one of these gene products, the C2-domain containing protein, Smurf1, are deficient in the autophagosomal targeting of Sindbis and herpes simplex viruses and in the clearance of damaged mitochondria. Moreover, Smurf1-deficient mice display an accumulation of damaged mitochondria in heart, brain, and liver. Thus, our study identifies candidate determinants of selective autophagy, and defines Smurf1 as a newly recognized mediator of both viral autophagy and mitophagy.